2022
DOI: 10.5811/westjem.2022.3.54663
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Point-of-Care Lung Ultrasonography: A Narrative Review

Abstract: Point-of-care lung ultrasonography is an evidence-based application that may play a vital role in the care of critically ill pediatric patients. Lung ultrasonography has the advantage of being available at the patient’s bedside with results superior to chest radiography and comparable to chest computed tomography for most lung pathologies. It has a steep learning curve. It can be readily performed in both advanced healthcare systems and resource-scarce settings. The purpose of this review is to discuss the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Similar results were also highlighted for family pediatricians. A possible explanation for this finding may be the steep learning curve which also allows novices to be able to perform lung US [ 25 ]. It should be also underlined that nearly one third of respondents assessed to use US for cardiac and abdominal application: traditionally, the use of US for these two anatomic regions is a prerogative of cardiologists and radiologists, respectively [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also highlighted for family pediatricians. A possible explanation for this finding may be the steep learning curve which also allows novices to be able to perform lung US [ 25 ]. It should be also underlined that nearly one third of respondents assessed to use US for cardiac and abdominal application: traditionally, the use of US for these two anatomic regions is a prerogative of cardiologists and radiologists, respectively [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…LUS can improve early diagnosis of lung diseases in critically ill children, being more sensitive than CXR and comparable to CT, without radiation exposure. Although it is operator dependent, different studies have shown that even beginners can perform it with high precision, showing adequate interobserver agreement in image interpretation [63,64]. Obesity and subcutaneous emphysema are the primary patient-related factors that can limit the effectiveness of LUS.…”
Section: Discussionmentioning
confidence: 99%
“…There is a limitation to using LUS for the location of pulmonary pathology since it cannot visualize the etiologies that do not extend to the pleural surface. However, more than 95% of pulmonary pathological processes have a pleural component in both adults and pediatric patients, making ultrasound useful in most cases [63,65].…”
Section: Discussionmentioning
confidence: 99%
“…As reflections occur at bone and air interfaces, diagnosis around those structures is often hindered. In addition, only a small part of the body can be examined simultaneously, and, most importantly, there is a strong dependence on the examiner and very few possibilities for post-hoc assessment of US images [ 6 ].…”
Section: Faster Than the Child’s Movement And The Movement Of The Hea...mentioning
confidence: 99%